E2F2/5/8 Serve as Potential Prognostic Biomarkers and Targets for Human Ovarian Cancer - Zhou, Quan; Zhang, Fan; He, Ze; Zuo, Man-Zhen (Frontiers in Oncology, 2019)
E2Fs is a family of pivotal transcription factors. Accumulative evidence indicated that aberrant expression or activation of the E2Fs is a common phenomenon in malignances, and the significant associations between E2Fs and tumorigenesis or progression in a wide range of cancers. However, the expression patterns and exact roles of each E2Fs contributing to tumorigenesis and progression of ovarian cancer (OC) are yet to be elucidated. In the current study, we report the distinct expression and prognostic value of E2Fs in patients with OC through analysis of a series of databases, including ONCOMINE, GEPIA, cBioPortal, Metascape and Kaplan–Meier plotter. It was found that mRNA expression levels of E2F1/2/3/5/8 were significantly upregulated in patients with OC, and obvious associated with tumor stage for OC. Aberrant expressions of E2F2/5/7/8 were found to be associated with the clinical outcomes of patients with OC. These results suggest that E2F2/5/8 may serve as potential prognostic biomarkers and targets for OC. However, future studies are required to validate our findings and thus promote the clinical utility of E2Fs in OC.